BUREAUCRATIC PROBLEMS AND CASES OF EMBEZZLEMENT OF STATE PROPERTY IN THE MANAGEMENT OF AGRICULTURE IN THE UZBEK SSR DURING 1960–1980 (Scientific journal of the Fergana State University, 2026)
This article analyzes the state and problems of the agricultural management system in the Uzbek Soviet Socialist Republic during the 1960–1980s. The impact of the strictly centralized and command-based administrative apparatus, typical of the Soviet period, on the agricultural sector is examined through historical sources. Factors such as the restriction of economic independence of farms, bureaucratic obstacles, and the artificial fulfillment of centrally assigned plans are explored. The article also analyzes cases of corruption and embezzlement of state property that emerged as a result of excessive centralization and ineffective control. Based on archival documents, statistical data, and historical analysis, the paper reveals the economic and social consequences of the governance mechanisms of that period.